Desenvolvimento tecnológico de suspensões e liofilizados de nanocápsulas poliméricas para a veiculação do neuroprotetor idebenona - Brendle, Martina Gehrke (2013)
Idebenone is an antioxidant, a synthetic derivative of coenzyme Q10, with several applications, such as neuroprotection. However, this drug has low solubility in water, besides is irritant substance and has chemical instability. Hence, idebenone-loaded nano-organized systems have been developed, such as polymeric nanocapsules (NC). Vegetable oils containing antioxidants such as coconut oil and palm oil can be interesting for the composition of these particles. In this way, the aim of this work was to develop NC suspensions containing different oils as core (palm, coconut or medium chain triglycerides) for delivery of neuroprotective agent idebenone in order to compare the behavior of these systems concerning physico-chemical stability, photostability, controlled release, and conversion to redispersible solid dosage forms (lyophilized products). The nanocapsules were prepared by interfacial deposition of preformed polymer. As the results, it was possible to prepare poly(Ɛ-caprolactone) NC suspensions and palm oil (PO/PCL) or Eudragit® RS100 and coconut oil (OC/EUD) containing idebenone (1.0 mg/mL) with appropriate physico-chemical characteristics. Parameters such as the proportion of aqueous phase/organic phase, type of both surfactant (low HLB) and polymer influenced the optimization of these systems. For comparison, corresponding formulations were prepared with medium chain triglycerides (TCM/PCL or TCM/EUD), using the same conditions. The suspensions had an average diameter between 166 and 216nm, low polydispersity index (0.085 to 0.142), positive or negative zeta potential, depending on the characteristics of the polymer, and high encapsulation efficiency. The maintenance of average particle diameter and low polydispersity index have be verified during stability study (room temperature and exposed or not to light) for 75 days. However, the idebenone content significantly decreased in this period, with influence on the type of polymer. Thereafter, photostability study has shown that the suspensions NC OP/PCL (UVC/UVA) and TCM/PCL (UVA) were able to significantly reduce the degradation of idebenone (content: 53,7-76,1%) compared to an aqueous micellar (content: 31,2-63,1%) dispersion containing the drug. In addition, these systems were able to promoting drug controlled release (t1/2 26 h), without burst effect, showing monoexponential profile (t1/2< 3.0 h for free drug). The lyophilization of suspensions, employing trehalose as soluble carbohydrate, resulted in suitable and redispersible products (content of 96-100%, less than 3.6% moisture; 0.8-1.2 index), presenting several spherical structures, including in colloidal range, featuring the presence of NC in these dried products. In the stability study (room temperature/protection from light and moisture), it was observed that the lyophilized products were able to delay or decrease the degradation of idebenone compared to suspensions of origin, regardless of the both type of polymer (PCL/EUD) and oil (OP/OC/TCM). In conclusion, the developed systems are promising for the controlled release of neuroprotective drug idebenone.